PROBLEMATIKA PEMBELAJARAN IPA PADA IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Syamsudin, Syamsudin; Fitriani, Siti Lailatul (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
The implementation of Kurikulum Merdeka is an educational approach that aims to provide greater freedom and flexibility to students in determining the course of learning. The changes seen in the independent learning curriculum are not required to use a thematic approach. So that each subject is separated according to the science of study and what is unique is that the learning of Natural Sciences (IPA) and Social Sciences (IPS) is combined into one as IPAs in Elementary Schools. The purpose of doing this research is to examine the problems of learning science in the implementation of Kurikulum Merdeka in Elementary Schools. By using a literature review and using existing data analysis, researchers found several facts including that there were still many teachers who did not fully understand the concept of independent learning, teachers had difficulties in determining approaches, models, strategies, methods to the science learning media to be used, and teachers had difficulty in assessing science subjects. Teachers also have difficulty integrating technology in science learning. For students, they are more likely to feel confused by the changing process of teaching and learning activities because the independent curriculum practice has only been implemented in grades I and IV only. In order to minimize all existing problems, commitment and collaboration of stakeholder are needed to achieve the full educational goals.